Instructional Design Framework for Construction Materials Training - Jadallah, Hazem; Friedland, Carol J.; Nahmens, Isabelina; Pecquet, Charles; Berryman, Charles; Zhu, Yimin (Frontiers in Built Environment, 2022)
The construction industry is suffering, in part, from a lack of training programs offered to the construction workforce. Unfortunately, most construction training and education research focuses on university student education. Integrating education science theory into construction workforce training has the potential to improve industry training but there is a dearth of studies that present details of this integration process. To address this gap, a training framework was developed to educate material stakeholders on material properties, selection, and installation. This framework is based on andragogical and Universal Design for Learning (UDL) principles. An assessment method evaluates training agendas to improve upon instructional design before training implementation. This method assesses the proposed training framework by enumerating the occurrences of Bloom’s Taxonomy verbs to determine how closely the proposed training’s goals and objectives followed Bloom’s guidelines. This study culminates by establishing linkages from educational theory to proposed training modules. The module template is presented in a goals and objectives format so that organizations can best implement and test this training framework.